How the ESRF helps industry and how they help the ESRF. (21st June 2013) - Malbet‐Monaco, Stéphanie; Leonard, Gordon A.; Mitchell, Edward P.; Gordon, Elspeth J.
<x xml:space="preserve">Abstract</x> The ESRF has worked with, and provided services for, the pharmaceutical industry since the construction of its first protein crystallography beamline in the mid‐1990s. In more recent times, industrial clients have benefited from a portfolio of beamlines which offer a wide range of functionality and beam characteristics, including tunability, microfocus and micro‐aperture. Included in this portfolio is a small‐angle X‐ray scattering beamline dedicated to the study of biological molecules in solution. The high demands on throughput and efficiency made by the ESRF's industrial clients have been a major driving force in the evolution of the ESRF's macromolecular crystallography resources, which now include remote access, the automation of crystal screening and data collection, and a beamline database allowing sample tracking, experiment reporting and real‐time at‐a‐distance monitoring of experiments. This paper describes the key features of the functionality put in place on the ESRF structural biology beamlines and outlines the major advantages of the interaction of the ESRF with the pharmaceutical industry.